Reciprocal regulation between DNMT3A/3B and microRNAs miRs-299-3p/-30e is a causal factor for the downregulation of microRNAs targeting androgen receptor in prostate cancer - Kavya Ganapathy; Christian F. Harrs; Samuel Harris; Stephen J. Staklinski; Ayman Khatib; Jong Y. Park; Ratna Chakrabarti (Heliyon)
Background: Promoter hypermethylation is one of the events that downregulate microRNAs (miRNA), resulting in the differential expression of genes implicated in the progression of cancer. We previously reported that microRNAs (miRNA)-299-3p and −30e target androgen receptor (AR) and are downregulated in advanced prostate cancer (PCa). Here we report that miR-34c, an AR targeting miRNA and miR-299-3p, both are differentially downregulated in PCa cells from African American (AA) and Caucasian American (CA) patients due to disparate promoter hypermethylation in these miRNA genes. Methods: We performed bisulfite sequencing based promoter methylation analysis with or without treatment with DNA methyl transferase (DNMT) inhibitor 5-Aza-2′-deoxycytidine (AzaC). Luciferase reporter assays and RNA pulldown assays are conducted for miRNA -DNMT interaction analysis. We performed DNMT activity assays and ectopic expression of miRNAs to study their effects. Results: We observed higher promoter methylation of these miRNA genes in cells derived from an AA patient compared to cells of CA origin, which can be reversed through AzaC treatment. Differential expression and activity of DNMT3A and 3B are noted in PCa cells from AA and CA origins. Immunoprecipitation of Ago revealed bound DNMT3A and 3B mRNAs with miRs-299-3p and −30e in the RISC. Luciferase reporter assays confirmed binding of miRs-299-3p and −30e to the UTRs of DNMT3A and 3B mRNAs. Overexpression of miRs-299-3p and −30e downregulated DNMT3A/B mRNA and protein expression and DNMT activity of DNMTs. Ectopic expression of miR-299-3p restored expression of miRs-34c and −30e in PCa cells. Similarly, overexpression of miR-30e restored expression of miRs-34c and -299-3p. Conclusion: Our study provides evidence that ectopic expression of miRs-30e and -299-3p restore the loss of expression of miRs-299-3p and −34c miRNAs mediated by DNMT-induced promoter hypermethylation. This study establishes a feedback regulation between AR targeting miRNAs and DNMTs in PCa cells and provides an insight into the mechanism of the aberrant expression of AR in advanced PCa that is potentially mediated through the downregulation of miRs-299-3p, −34c and −30e and stabilization of expression and activities of DNMTs.